Exploring public perceptions of prototype rural landscapes in contemporary China: a survey-based study; [Explorando as percepções públicas dos protótipos de paisagens rurais na China contemporânea: um estudo baseado em pesquisas] - Shaohua, Liu; Mohd Ali, Noor Azizi; S. Muthuveeran, Adam Aruldewan (Federal University of Mato Grosso, 2023)
The present study delves into the public perceptions concerning prototype rural landscapes in China, aiming to unravel respondents’ varied layers of appreciation, concerns, and aspirations. Employing a quantitative approach through a structured questionnaire, the survey collected insights from a diverse demographic to unveil compelling facets of rural landscape perceptions. The findings revealed a collective admiration for cultural heritage preservation, natural beauty, and traditional architectural styles within rural settings. However, amidst this appreciation, concerns regarding infrastructural deficiencies, environmental sustainability, and socio-economic disparities emerged. These insights underscore the necessity of integrating public perceptions into future landscape planning endeavors to develop culturally resonant, sustainable and community-centric rural landscapes. Recommendations for future research highlight avenues for deeper exploration, emphasizing the need for innovative strategies to bridge infrastructural gaps, enhance environmental sustainability, and empower communities in shaping the future of rural landscapes in China.